Organizational Learning Capability, Firm Innovation, Knowledge Management Effectiveness, and Sustainable Competitiveness: A Conceptual Model - Phornlaphatrachakorn, Kornchai (KKBS Journal of Business Administration and Accountancy, 2017)
This study aims at presenting the relationships among organizational learning capability, firm innovation, knowledge management effectiveness, and sustainable competitiveness. Firstly, organizational learning capability is proposed to have a relationship with firm innovation and sustainable competitiveness. Secondly, firm innovation is considered to have a positive effect on sustainable competitiveness. Lastly, it is likely that knowledge management effectiveness could become a moderator for the organizational learning capability-firm innovation relationship, the organizational learning capability-sustainable competitiveness relationship and the firm innovation-sustainable competitiveness relationship. In summary, organizational learning capability plays a significant role in determining both firm innovation and sustainable competitiveness through moderating effects of knowledge management effectiveness. To verify the proposed research relationships, future research should collect data from real businesses in order to investigate the relationships. Contributions via theoretical and managerial aspects, limitations of the study and conclusion are presented.